Developing Research and Study Courses (RSC) in the pre-service teacher education - Otero, Maria Rita (2017)
In this paper, we present results of an implementation of research and study course carried out into a teacher training course in the University. The framework of the Anthropological Theory of the Didactic (ATD) is adopted, and a co-disciplinary Research and Study Path (RSP) whose generative question requires studying mathematics and physics together is carried out by training teachers of Mathematics at University. Some conclusions concerning on the conditions, restrictions and relevance of introducing the RSP in teachers training courses at the university are presented.